2022
DOI: 10.1002/trc2.12274
|View full text |Cite
|
Sign up to set email alerts
|

A novel process driving Alzheimer's disease validated in a mouse model: Therapeutic potential

Abstract: Introduction The neuronal mechanism driving Alzheimer's disease (AD) is incompletely understood. Methods Immunohistochemistry, pharmacology, biochemistry, and behavioral testing are employed in two pathological contexts—AD and a transgenic mouse model—to investigate T14, a 14mer peptide, as a key signaling molecule in the neuropathology. Results T14 increases in AD brains as the disease progresses and is conspicuous in 5XFAD mice, where its i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…In relation to melatonin, it has been evaluated in clinical assays related to cranial nerve diseases, multiple sclerosis, epilepsy, sleep disorders, spinal cord injuries, migraine, trauma brain injury, dementia, Huntington, Alzheimer and Parkinson Diseases [ 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 ]. Of note, some of these diseases have also been studied in experimental models, evaluating the neuroprotective effect of these compounds mainly by their antioxidant and anti-inflammatory properties [ 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 ]. Moreover, the effects of quercetin, melatonin and curcumin have been explored in obese patients in different studies, but they have not proposed gliosis as an important comorbidity [ 2...…”
Section: Protective Role Of Antioxidants In Gliosismentioning
confidence: 99%
“…In relation to melatonin, it has been evaluated in clinical assays related to cranial nerve diseases, multiple sclerosis, epilepsy, sleep disorders, spinal cord injuries, migraine, trauma brain injury, dementia, Huntington, Alzheimer and Parkinson Diseases [ 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 ]. Of note, some of these diseases have also been studied in experimental models, evaluating the neuroprotective effect of these compounds mainly by their antioxidant and anti-inflammatory properties [ 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 ]. Moreover, the effects of quercetin, melatonin and curcumin have been explored in obese patients in different studies, but they have not proposed gliosis as an important comorbidity [ 2...…”
Section: Protective Role Of Antioxidants In Gliosismentioning
confidence: 99%
“…We have previously reported the presence of AChE in the pars compacta, pars reticulata and extracellular space of the SN at light- and electron-microscopic levels [ 44 ]. The present immunohistochemical studies used a polyclonal antibody against T14 that requires an exposed COOH-terminal lysine, thereby precluding the detection of AChE, the parent molecule, or amyloid, with which T14 has a partial sequence homology [ 35 , 42 ]. Accordingly, we have identified free T14 in pars compacta neurons of the mouse SN; these were shown to be dopamine neurons by the colocalization of tyrosine hydroxylase.…”
Section: Discussionmentioning
confidence: 99%
“…T30 is a 30-mer peptide from the C-terminus of AChE; it includes T14 as the active component and is more stable than the smaller peptide in solution [ 31 ]. T14 and T30 act via alpha-7 receptors [ 30 , 31 ], enhancing calcium entry through an allosteric site [ 30 ] and triggering the accumulation of phosphorylated Tau and amyloid beta [ 35 , 42 ]. Previous studies using various experimental preparations have demonstrated that the binding of T14 or T30 to alpha-7 receptors can be blocked by NBP14, a cyclized variant that displaces the peptide from its receptor [ 33 , 35 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations